Strategies for Developing Cycling Tourism in Urban Communities Based on Characteristics of Motivation - Laksmana, Tb.Adinda; Mulan, Kencan; Endyana, Cipta; Rachmat, Heryadi (Timorese Journal of Public Health, 2023)
Sports for some people are not only a necessity of daily life but also have been considered a lifestyle. Aside from being a regular alternative to keeping the body fit, it has many other benefits. The rapid development of this lifestyle of sports in urban communities is characterized by the increasing number of community groups that routinely do the type of exercise that can be done in between the limitations of time. Cycling is one of the activities that are much in demand by urbanites, as this type of sport activity gives both convenience and an outlet for an engaging fun. The emergence of cycling groups in urban communities is a reflection of the need for exercise routines that also provides outdoor recreation. There are various kinds of motivations for cyclists, from just wanting to exercise, to travel, to save fuel and avoid traffic, to minimize the effects of air pollution, or to look for new experiences and challenges, including new friendships or as an output of self-actualization. This research uses a qualitative descriptive phenomenological method, as well as a non-random purposive sampling technique on two urban bicycle groups, namely TOC and JGS-SCAM. Data collection was done by using the Google questionnaire application and the data was analyzed interactively by the model of Miles, Huberman, Saldaňa, and the application of second cycle data coding. The questionnaire results obtained were able to classify and characterize the urban cyclists based on their characteristics and motivation, and also determined the strategies for developing urban cyclist tourism by analyzing internal IFAS and external EFAS factors from the motivational characteristics of the urban cyclist, then the strategies were determined by using the SWOT method, ultimately cummulating into plans to develop a cycling tourism for urban communities.